2021
DOI: 10.3389/feart.2021.799935
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Environmental Changes Inferred From an Aeolian-Palaeosol-Lacustrine Profile in the Mu Us Desert, Northern China

Abstract: An excavated profile of aeolian-palaeosol-lacustrine sediments (the Wapianliang profile), located at the southeastern part of the Mu Us Desert, Northern China, was studied to reconstruct regional Holocene environmental changes. A chronology was established based on three AMS 14C and two OSL dates, and variations in the lithology and grain size, magnetic susceptibility, soil micromorphology, and chemical elements were used to explore the regional depositional environments during the Holocene. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These observations suggest that climate alone was not adequate as the driving force of sediment dynamics and soil erosion. Previous studies demonstrated a similar monsoon-dominated variation pattern of the Holocene climate [53][54][55][56][57][58][59][60][61] and a similar magnetic enhancement model for typical loess across the CLP [48,50,54]. Based on the aforementioned fluctuations in and weakening relation between the proxies, an age frame for the Sanmenxia section is attained by interpolation with the ages of 12.9 ka, 11.7 ka, 8.2 ka, 7.8 ka, 5.9 ka, and 4.2 ka being assigned to the depth at 5.7 m, 4.25 m, 3.2 m, 2.98 m, 2.5 m, and 1.62 m, respectively (Figure 10).…”
Section: Decoupling From Climatic Evolution Since 4 Kamentioning
confidence: 80%
“…These observations suggest that climate alone was not adequate as the driving force of sediment dynamics and soil erosion. Previous studies demonstrated a similar monsoon-dominated variation pattern of the Holocene climate [53][54][55][56][57][58][59][60][61] and a similar magnetic enhancement model for typical loess across the CLP [48,50,54]. Based on the aforementioned fluctuations in and weakening relation between the proxies, an age frame for the Sanmenxia section is attained by interpolation with the ages of 12.9 ka, 11.7 ka, 8.2 ka, 7.8 ka, 5.9 ka, and 4.2 ka being assigned to the depth at 5.7 m, 4.25 m, 3.2 m, 2.98 m, 2.5 m, and 1.62 m, respectively (Figure 10).…”
Section: Decoupling From Climatic Evolution Since 4 Kamentioning
confidence: 80%
“…In this regard, organic fertilizers play a pivotal role by enhancing soil microbial activity within the maize rhizosphere. This heightened microbial activity, as evidenced by prior research, leads to the acceleration of the decomposition and mineralization of organic matter ( Liu et al., 2021 ). The CF, DF, and MF treatments produced significant alterations in the bacterial community structure, with the CF treatment exhibiting a community structure similar to that of the CK treatment ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 91%
“…Maize ( Zea mays L. ) has traditionally been cultivated in Mu Us Sandy Land. Nevertheless, in recent years, the introduction of land consolidation technology has enabled the expansion of maize cultivation from the southern desert periphery into the inland areas, leading to a transition from scattered to large-scale farming ( Liu et al., 2021 ). Unfortunately, the establishment of extensive maize cultivation areas often involves the flattening of undulating sand dunes and the mixing of sand with other soil types.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the grain-size component is assumed to reflect fluctuations in the lake level. The aeolian sand component (38-418 μm) is transported by saltation or rolling when strong surface wind occurs (e.g., Qiang et al, 2010;Dietze et al, 2014;Mou et al, 2018;Liu et al, 2021). Moreover, this transport of aeolian sand on frozen lakes is associated with strong winds that particularly occur during winter and early spring storms (Sun et al, 2002).…”
Section: Grain-size Componentsmentioning
confidence: 99%
“…Most studies suggest that the warm and wet Mid-Holocene was widely recorded in the arid and semiarid areas of China (e.g. Feng et al, 2006; Liu et al, 2018; Feng and Yang, 2019; Wang et al, 2019; Gao et al, 2020; Liu et al, 2021; Ning et al, 2021; Peng et al, 2022; Chen et al, 2023). However, some studies suggest that a dry Mid-Holocene climate has been found in desert regions of arid and semiarid China (such as the Tengger Desert, the Hobq Desert, and the Taklimakan Desert) (see An et al 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%